Organizational Resilience in Hospitality and Tourism - Rozkwitalska, Malgorzata; Borzyszkowski, Jacek; Basi?ska, Beata Aleksandra; Okumus, Fevzi; Karatepe, Osman M. (Taylor and Francis, 2024)
Although ‘VUCA’ is not a new term, the features of the world it describes, a volatile, uncertain, complex and ambiguous environment, have never been more valid. The VUCA world has become the new reality for business, specifically for hospitality and tourism organizations that are more vulnerable than any other sector due to the historically-recognized turbulent environment in which they operate. In this book, the authors present unique factors that make hospitality and tourism organizations resilient in the VUCA world. With contacts at the center of their hospitality and tourism organizational resilience model, the organizational and psychological perspectives are also incorporated. This innovative volume tests the model of organizational resilience in hospitality and tourism organizations. The study identifies and validates organizational and individual factors that create a resilient organization in the hospitality and tourism sector. It will be of interest to researchers, academics, practitioners, and advanced students in the fields of organizational studies, strategic management, hospitality, and tourism management. © 2024 Malgorzata Rozkwitalska-Welenc, Jacek Borzyszkowski, Beata A. Basinska, Fevzi Okumus and Osman M. Karatepe.